Rescue of type I collagen-deficient phenotype by retroviral-vector-mediated transfer of human pro alpha 1(I) collagen gene into Mov-13 cells. - Stacey, A (1987)
A full-length cDNA clone corresponding to the human pro alpha 1(I) collagen gene was isolated and inserted into a retrovirus vector. Cell lines were obtained which produced recombinant viruses transducing the collagen cDNA (HUC virus). To test whether the transduced cDNA was functional, Mov-13 mouse cells were infected with the virus. These cells do not produce any type I collagen due to an insertional mutation of the pro alpha 1(I) gene which blocks transcription. While normal amounts of pro alpha 2(I) RNA were synthesized, no alpha 2(I) collagen chains were detectable in the mutant Mov-13 cells. Infection with HUC virus, however, resulted in the production of stable type I collagen, which was secreted into the medium. Analysis of pepsin-resistant proteins indicated that interspecies heterotrimers consisting of human alpha 1(I) and mouse alpha 2(I) collagen chains were secreted by the infected Mov-13 cells. Our results show that pro alpha (I) collagen chains from species as distant as human and mouse can associate to form stable type I collagen. The availability of a retrovirus vector transducing a functional pro alpha 1(I) collagen gene combined with the Mov-13 mutant system should enable us to study the effect of specific mutations on the synthesis, assembly, and function of type I collagen, not only in tissue culture but also in the animal.